Exploring Children's Induced Defensiveness to the Tell Me a Story Test (TEMAS). Issue 3 (4th May 2017) - Fantini, Francesca; Banis, Aglaia; Dell'Acqua, Erica; Durosini, Ilaria; Aschieri, Filippo
ABSTRACT: This study examined the effect of inducing a defensive attitude (fake good) in children on their responses to the Tell Me a Story test (TEMAS; Costantino, Malgady, & Rogler, 1988 ). Different story elicitation procedures were employed to explore their efficacy for inducing a defensive response style in children. Eighty-four Italian children aged 8 to 10 years old completed the TEMAS and the L scale of the Behavioral Assessment Scale for Children–2 (BASC–2; Reynolds & Kamphaus, 2004 ), which were used to detect the adoption of a defensive attitude. Children completed the tests under 1 of 3 conditions: (a) honest condition, (b) fake good with verbal instructions, and (c) fake good with verbal instructions and visual stimuli illustrating what was verbally explained. Using simultaneous verbal instructions and visual stimuli facilitated children's understanding of the researcher's instructions compared to using verbal stimuli alone. Results showed that children instructed to fake good used less time to tell stories and tended to modify the simpler and more face valid aspects of their stories. Still, 29 out of 47 children failed to fake good on the BASC–2 L scale. More complex TEMAS variables showed no significant difference between story elicitation conditions.